2001
DOI: 10.2460/ajvr.2001.62.1776
|View full text |Cite
|
Sign up to set email alerts
|

Activation-induced mobilization of secretory vesicles in bovine neutrophils

Abstract: Bovine neutrophils respond to various inflammatory mediators by mobilizing alkaline phosphatase-containing secretory granules. This suggests that the process is an important early step in the host-defense response of bovine neutrophils.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 43 publications
0
1
0
Order By: Relevance
“…The increase of NAP upon bacterial infection suggests that NAP might be closely related to neutrophils' function and the regression of inflammation. Steve D et al [22] found bovine neutrophils respond to various inflammatory mediators by mobilizing alkaline phosphatase-containing secretory granules, which suggested that the process was an important early step in the host-defense response of bovine neutrophils.…”
Section: Discussionmentioning
confidence: 99%
“…The increase of NAP upon bacterial infection suggests that NAP might be closely related to neutrophils' function and the regression of inflammation. Steve D et al [22] found bovine neutrophils respond to various inflammatory mediators by mobilizing alkaline phosphatase-containing secretory granules, which suggested that the process was an important early step in the host-defense response of bovine neutrophils.…”
Section: Discussionmentioning
confidence: 99%
“…The cells of the innate and adaptive immune systems are both identified to be influenced by E 2 (Blesson, 2011;Karpuzoglu and Zouali, 2011;Dragin et al, 2017). El-Banna and Hafez (1972) and Marinov and Lovell (1967) have proposed that E2 serum levels are reported to be lowest during the estrus stage of the estrous cycle causing cervical mucus to be secreted in bovines. Accordingly, Kumar et al (2021) identified that the serum concentration of E 2 in normal estrus Murrah buffaloes (animals showing signs of heat) was significantly higher when compared to the silent estrus animals (animals not showing signs of heat).…”
Section: Urinary Exosome Shbg Levels In G-i G-ii and G-iii Animalsmentioning
confidence: 99%
“…The results of the present study are in contrast to the findings of Vesanen et al (1990) who reported the circulatory levels of SHBG at the estrus as well as diestrus stage to be almost similar. Further, it appears that the significantly lower levels of SHBG in urinary exosomes of G-II and G-III animals could be due to lower levels of circulatory SHBG at the estrus stage (Mousavi and Adlercreutz, 1993;Hammond, 2002;Wallen and Hassett 2009), as E 2 needs to exert its action in the female reproductive tract (Marinov and Lovell 1967;El-Banna and Hafez, 1972).…”
Section: Quantification Of Urinary Exosome Sex Hormone Binding Globul...mentioning
confidence: 99%